2010
DOI: 10.3122/jabfm.2010.06.090271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Sick Child after Travel to Developing Countries

Abstract: Every year, millions of children travel internationally with their families, many to developing countries. Although the vast majority experience uneventful travel and return home well, it is not uncommon for children to present as ill during or after travel. Although the majority of travel-associated illness is mild and self-limited, serious conditions regularly occur. Almost all life-threatening conditions after travel present with fever, and malaria is the most important of these to rapidly exclude. Gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
7
1
3
Order By: Relevance
“…In our study, the percentage of hospitalisations in child travellers was higher than that found in a multicentre study (14% of travelling children) 9. Diarrhoea and fever also accounted for the majority of diagnoses reported in children without SCD 9 10…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, the percentage of hospitalisations in child travellers was higher than that found in a multicentre study (14% of travelling children) 9. Diarrhoea and fever also accounted for the majority of diagnoses reported in children without SCD 9 10…”
Section: Discussioncontrasting
confidence: 65%
“…Other studies show bacterial infections as the most prevalent cause of GI symptoms. 19 Laboratories of different centers attending post-travel diseases also use different techniques to study these infections. This fact could justify some of these controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…Cuanto más largo sea el intervalo entre el regreso y el inicio de los signos, menos riesgo existe de que la sintomatología tenga relación con el viaje; • la existencia de otras personas del entorno con una sintomatología comparable. Deben precisarse las características del viaje [19][20][21][22][23][24][25] [19] ), especialmente graves y contagiosas, algunas de las cuales podrían justificar medidas de aislamiento inmediatas del viajero sospechoso, incluso antes de la confirmación microbiológica. Es posible informarse de las epidemias en curso en numerosos sitios web, como los de la Organización Mundial de la Salud (OMS) o el Ministerio de Asuntos Exteriores francés (Cuadro 1); • duración de la estancia: cuanto más prolongada sea la estancia, más aumenta la exposición al riesgo, sobre todo en medio tropical; • fecha de regreso (o de salida de la zona de riesgo): es importante compararla con la del inicio de los signos para definir el período de incubación, que puede orientar el diagnóstico.…”
Section: Anamnesisunclassified